The Influence of Perceived Ease of Use on Impulsive Buying With Lifestyle as Moderation - Puspitaningtias, Rofi; Afriani, Lita Ningrum (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aim to know that Influence Of Perceived Ease Of Use On Impulsive Buying With Lifestyle As Moderation. The Result in this study know that based on the results of data analysis, hypotheses one and two are accepted while hypothesis 3 is rejected. Thus, perceived ease of use influences impulsive buying, this shows that perceived ease of use encourages impulsive buying. The results of this research are different from previous research conducted by (Purnamasari, Sasana, & Novitaningtyas, 2021) that perceived ease of use has a negative influence on the decision to use the SPaylater payment method.